An Overview: PM2.5 Concentration Levels in Urban Residential Buildings during the Past Two Decades - Yu Liu; Jiankai Dong; Hongqiang Ma; Yiqiang Jiang; Wenke Zheng; Xinmei Luo (Aerosol and Air Quality Research)
Abstract The public has become increasingly aware of the critical effect of fine particle matter (PM2.5) on indoor air quality. Urban residents spend more than half of their time at home. Therefore, monitoring PM2.5 concentrations in residential settings is critical. This paper presents a review of studies on PM2.5 concentrations in the living rooms of urban residential buildings. We included studies measuring indoor PM2.5 concentrations across different regions worldwide and then summarized the measured concentrations. Factors contributing to differences in indoor concentrations were identified and explained. The review results revealed that most of the included studies were conducted in Asia and in Europe, and some were conducted in North America and Africa. Moreover, the mean daily PM2.5 concentration ranged from 17.3 µg m−3 in North America to 68.6 µg m−3 in Asia. Factors influencing PM2.5 concentrations were as follows: indoor activities, ventilation type and air cleaner (AC) use, building type and performance, ambient environment and season. Smoking and cooking considerably increased PM2.5 concentrations in the living rooms, even in measurements conducted over a short time. The use of an AC could reduce indoor PM2.5 concentration in an average of 60%. Regarding building type, PM2.5 concentration in multifamily apartment buildings had higher PM2.5 concentrations than did single-room residences. Moreover, severe outdoor particle pollution increased indoor PM2.5 concentrations by up to 142% in low-energy residential buildings.